(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2019)
In the clinical context, therapist’s behaviors and the relationship that he/she establishes with the client are not only relevant but may facilitate or prevent the development of the therapeutic process. From a narrative review, the present study aimed to present some contributions of the mindfulness practice for the development of therapeutic skills. Thus, from the conceptual foundations of mindfulness and clinical practice in psychology, it was discussed how the mindfulness practice can facilitate the development of therapeutic skills. The five elements model proposed by Baer, Smith, Hopkins, Krietemeyer and Toney (2006), Zarbock et al. (2015), and Fulton’s (2016) considerations on mindfulness skills were used. It was pointed out that learning mindfulness practices can benefit clinical services by strengthening the therapeutic rapport between client and therapist, as well as creating a non-punitive audience for events that occur during the therapeutic process through acceptance and “beginner’s mind” strategies.